The Role of Pre-Procedural Ultrasound Examination for Anesthesia: Case Series - Steven Yoe; Tommy Nugroho Tanumihardja; Yuliana; Bernardus Realino Harjanto; Pangkuwidjaja Partahusniutojo (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2025)
Ultrasonography is an ultrasound-based imaging technique which are utilized to visualize subcutaneous structures. In anesthesiology, ultrasonography is widely used for finding vascular access, nerve block and regional anesthesia, trans esophageal echocardiography (TEE), and epidural space measurement. Ultrasonography is a relatively safe, non-invasive, and easily accessible imaging modality which also provides ease of anatomical evaluation for anesthesiologists before a procedure. In the first case, a 55 years old man with chronic renal failure undergoing arteriovenous fistula procedure was examined with ultrasonography for brachial plexus block. In the second case, a 63 years old man with acute kidney injury (AKI) was examined with ultrasonography of the right jugular and right subclavian veins to identify vascular access for double lumen catheter insertion. In conclusion, the use of ultrasonography before peripheral nerve block procedures and central venous catheter placement can help anesthesiologist to determine the nerves to be blocked and determine the right vein for catheter insertion.